A Discourse Analysis of Cyber Socialising Interactions in English among Students - Tiyiselani Ndukwani; Runash Ramhurry (Asosiasi Dosen Perguruan Tinggi Islam, 2023)
The influence of technology and engagement in cyber socializing has become a prominent part of modern communication. A new learning pedagogy with proper guidelines is needed to assist users in engaging with social networking platforms efficiently. The researchers investigated discourse analysis involving participants to answer questions about the contextual application of the language and the functions and results of aspects of discourse such as diction, cohesion, and metaphors. The researchers employed a quantitative approach in this study. The study randomly sampled 80 students from the University of Technology in Gauteng to participate in quantitative discourse analysis of communication using Facebook, WhatsApp, and Twitter texts. The data elicitation methods embraced extracts from Facebook, WhatsApp, and Twitter texts provided by 80 participants. Data were collected via email, and texts were numbered according to the participants. These texts remain anonymous, and the identities of the participants are concealed. The study found that the use of emoji characterized the language used on Facebook, WhatsApp, and Twitter, low register words, code-switching, few spelling errors, and the modern tendency to shorten words by using clipping and number homophones, which are not seen as errors but a unique style of writing.